Equine bone marrow‐derived mesenchymal stromal cells (BMDMSCs) from the ilium and sternum: Are there differences?. (26th September 2012) - Adams, M. K.; Goodrich, L. R.; Rao, S.; Olea‐Popelka, F.; Phillips, N.; Kisiday, J. D.; Mcilwraith, C. W.
Summary Reasons for performing study The 2 sites of bone marrow harvest for isolation of mesenchymal stromal cells (MSC) in the horse are the sternum and ilium. The technical procedure is based on practitioner preference, but no studies have compared MSC concentrations and growth rates between the sites in horses aged 2–5 years. Objectives The objective of this study was to compare nucleated cell counts and growth rates between the sternum and ilium and between consecutive 5 ml bone marrow aspirates. We hypothesised that there would be a higher concentration of MSCs in the sternum than the ilium, and that the first sequential aspirate from either site would yield the greatest concentration of MSCs. We hypothesised that growth rates of cells from each site would not differ. Methods Seven horses, aged 2 to 5 years, had 2 sequential 5 ml marrow aspirates taken from the sternum and ilium. Nucleated cell counts (NCCs) were obtained before and after marrow processing. Cells were expanded in culture for 3 passages and growth rate characteristics compared for all aspirates. Results The NCCs of the first 5 ml aspirate were higher than those of the second 5 ml aspirate for both sites (P<0.05). There was no difference between growth rates for any of the groups (P>0.05). Conclusions The NCCs and growth rates of progenitor cells in the ilium and sternum are similar for horses in the 2–5 year age category. The first 5 ml bone marrow aspirate has a higher concentration of NCCs and resulting bone marrow‐derived MSC population than subsequent aspirates. Potential relevance The first 5 ml aspirates from the sternum and ilium offer a rich supply of bone marrow‐derived MSCs with similar growth rate characteristics. The harvesting procedure of only a 5 ml draw from either the sternum or ilium should result in adequate numbers of MSCs.